2017
DOI: 10.1038/s41598-017-06261-5
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom lectin overcomes hepatitis B virus tolerance via TLR6 signaling

Abstract: Currently, chronic hepatitis B virus (HBV) infection remains a serious public health problem in the world. Recombinant HBV vaccine, as a preventive strategy against HBV infection, generates high antibody level, but it is not effective to activate innate and cellular immunity for chronic HBV infection therapy. Lectins from mushroom are natural and active proteins which have been shown important biological functions. However, little is known about the immunological mechanism engaged by mushroom lectins. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The in vivo immunomodulatory effects of lectin isolated from A. bisporus was also studied [190]. Lectin from P. ostreatus (POL) stimulated an immune response and has been considered as a potential therapeutic approach to break HBV tolerance [191]. It has also been shown to act as a food-intake-suppressing substance, which can help in weight reduction [192].…”
Section: Proteinsmentioning
confidence: 99%
“…The in vivo immunomodulatory effects of lectin isolated from A. bisporus was also studied [190]. Lectin from P. ostreatus (POL) stimulated an immune response and has been considered as a potential therapeutic approach to break HBV tolerance [191]. It has also been shown to act as a food-intake-suppressing substance, which can help in weight reduction [192].…”
Section: Proteinsmentioning
confidence: 99%
“…Regarding many fungal crude extracts and their enzymes, the antiviral effect of fungal lectin against HIV was the most investigated virus. El-Maradny et al [194] indicated that the purified Trichogin protein from Tricholoma giganteum was found to inhibit the HIV reverse transcriptase (RT) enzyme with the lowest IC 50 (half maximal inhibitory concentration) value determined to be 83 nM [195], followed by the purified lectin from Russula delica with IC 50 value of 0.26 [75] and the purified laccase from Tricholoma mongolicum with IC 50 value of 0.62 µM [196]. Lectins bind with viral envelope glycoproteins and inhibit the entry of many viruses, such as HIV, thus inhibiting virus attachment and blocking its entry via inducing the virus conformational rearrangements [197].…”
Section: Biomedical Applications 431 Antimicrobialmentioning
confidence: 99%
“…In an acute HBV replication mouse model, flagellin protein as a bacterial PAMP plays a pivotal role in regulating intrahepatic CD8 + T-cell responses by activating the TLR5 pathway (Yan et al, 2020). TLR6 overcome HBV tolerance in the CHB mouse models by enhancing HBV-specific antibody levels and follicular-assisted T-cell responses (He et al, 2017). This study proposes a novel mechanism by which TLR6 acts on the immune response and a therapeutic approach that breaks down the tolerance of HBV.…”
Section: Tlr Agonist-mediated Therapeutics For Controlling Hbv Replic...mentioning
confidence: 91%